2017
DOI: 10.1073/pnas.1704699114
|View full text |Cite
|
Sign up to set email alerts
|

Electron localization in rod-shaped triicosahedral gold nanocluster

Abstract: Atomically precise gold nanocluster based on linear assembly of repeating icosahedrons (clusters of clusters) is a unique type of linear nanostructure, which exhibits strong near-infrared absorption as their free electrons are confined in a one-dimensional quantum box. Little is known about the carrier dynamics in these nanoclusters, which limit their energy-related applications. Here, we reported the observation of exciton localization in triicosahedral Au nanoclusters (0.5 nm in diameter and 1.6 nm in length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 54 publications
7
84
0
Order By: Relevance
“…Two frequencies (40 cm −1 and 80 cm −1 ) were exhibited at different probe wavelengths ( Figure 6D), which have been reported previously [51]. These oscillations observed in TA decays, also observed in other nanoclusters [52,53], were assigned to acoustic vibrations of the metal core and explained as displacive excitation [52,54], similar to that observed in semiconductors and small molecules [54,55].…”
Section: Resultssupporting
confidence: 85%
“…Two frequencies (40 cm −1 and 80 cm −1 ) were exhibited at different probe wavelengths ( Figure 6D), which have been reported previously [51]. These oscillations observed in TA decays, also observed in other nanoclusters [52,53], were assigned to acoustic vibrations of the metal core and explained as displacive excitation [52,54], similar to that observed in semiconductors and small molecules [54,55].…”
Section: Resultssupporting
confidence: 85%
“…As a building block, this unit can be assembled into different supramolecular structures by controlling the capping ligands . Different assembly forms of the M 13 unit not only contribute to the construction of superatomic aggregates with novel structures, but also have a remarkable effect on the optical, catalytic, and other properties of the superatomic aggregates . This greatly encourages us to continue exploring the superatomic assembly of M 13 elements …”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on gold/silver metal superatomic clusters based on the assembly of M 13 units, which have become a new class of nanomaterial and shown intriguing properties . Benefiting from single‐crystal X‐ray crystallography, the well‐determined structures have explicitly revealed the surface structure, the type of bonding, and the assembly method for nanoclusters consisting of M 13 units .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary and perspective : With introducing two groups of elementary blocks in the GUM, Au 3 (2 e ), and Au 4 (2 e ), a variety of ligand-protected gold nanoclusters, e.g., spherical and non-spherical, or magic-number and non-magic-number, can be viewed as an aggregate of the elementary groups by applying electron counting rule, a notion analog to Mingo’s united atom model for understanding weakly bound condensed icosahedra with 8 e valence electrons for each unit 7 . A recent experiment showed that the localization effect is highly important for the interpretation of the spectroscopy of gold nanoclusters 8 . Moreover, the triangle Au 3 and tetrahedral Au 4 can be considered as the basic units of face-centered cubic bulk gold.…”
Section: Introductionmentioning
confidence: 99%